Option prices and costly short-selling - Atmaz, Adem; Basak, Suleyman (Journal of Financial Economics, 2019)
Much empirical evidence shows that stock short-selling costs and bans have significant effects on option prices. We reconcile these findings by providing a dynamic analysis of option prices with costly short-selling and option market makers. We obtain simple, closed-form, unique option bid and ask prices that represent option market makers’ expected hedging costs, and are weighted averages of well-known benchmark prices (Black–Scholes, Heston). Our analysis delivers rich implications that support the empirical evidence on the effects of short-selling costs and bans on option prices, as well as uncovering several novel predictions. We also apply our methodology to corporate bonds, which have option-like payoffs.